Differential effects of allopregnanolone and diazepam on social behavior through modulation of neural oscillation dynamics in basolateral amygdala and medial prefrontal cortex - Yawata, Yosuke; Tashima, Ryoichi; Aritomi, Hiroyuki; Shimada, Shinji; Onodera, Tsukasa; Taishi, Teruhiko; Takasu, Keiko; Ogawa, Koichi (Frontiers in Cellular Neuroscience, 2024)
Effective treatments for major depressive disorder (MDD) have long been needed. One hypothesis for the mechanism of depression involves a decrease in neuroactive steroids such as allopregnanolone, an endogenous positive allosteric modulator of the γ-aminobutyric acid-gated chloride channel (GABAA) receptor. In our previous study, we discovered that allopregnanolone, not diazepam, exhibited antidepressant-like effects in the social interaction test (SIT) of social defeat stress (SDS) model mice.However, the dynamics of neuronal activity underlying the antidepressant-like effect remain unknown.In the current study, we conducted local field potentials (LFPs) recordings from the basolateral amygdala (BLA) and the medial prefrontal cortex (mPFC) during the SIT to elucidate the relationship between the antidepressant-like effect and neuronal oscillation. We discovered that allopregnanolone has antidepressant-like effects in the SIT of SDS model mice by decreasing intervals of repetitive social interaction (inter-event intervals), resulting in increase of total social interaction time. We also found that theta and beta oscillation increased in BLA at the onset of social interaction following administration of allopregnanolone, which differed from the effects of diazepam. Theta and beta power in BLA within the social interaction zone exhibited a positive correlation with interaction time. This increase of theta and beta power was negatively correlated with inter-event intervals. Regarding thetaband coordinated activity between the BLA and mPFC, theta power correlation decreased at the onset of social interaction with the administration of allopregnanolone. These findings suggest that theta activity in BLA following social interaction and the reduced theta-band coordinated activity between the BLA and mPFC are implicated in social interaction, which is one of the antidepressant behaviors.These difference in neural activity could elucidate the distinctive mechanism underlying antidepressant-like effects of neuroactive steroids, as opposed to benzodiazepines.